Differential microRNA Expression in Fast- and Slow-Twitch Skeletal Muscle of Piaractus mesopotamicus during Growth - Silva Duran, Bruno Oliveira da [UNESP]; Fernandez, Geysson Javier [UNESP]; Mareco, Edson Assuncao [UNESP]; Moraes, Leonardo Nazario [UNESP]; Simoes Salomao, Rondinelle Artur [UNESP]; Paula, Tassiana Gutierrez de [UNESP]; Santos, Vander Bruno; Carvalho, Robson Francisco [UNESP]; Dal-Pai-Silvca, Maeli [UNESP] (Public Library Science, 2015)
Pacu (Piaractus mesopotamicus) is a Brazilian fish with a high economic value in pisciculture due to its rusticity and fast growth. Postnatal growth of skeletal muscle in fish occurs by hyperplasia and/or hypertrophy, processes that are dependent on the proliferation and differentiation of myoblasts. A class of small noncoding RNAs, known as microRNAs (miRNAs), represses the expression of target mRNAs, and many studies have demonstrated that miR-1, miR-133, miR-206 and miR-499 regulate different processes in skeletal muscle through the mRNA silencing of hdac4 (histone deacetylase 4), srf (serum response factor), pax7 (paired box 7) and sox6 ((sex determining region Y)-box 6), respectively. The aim of our work was to evaluate the expression of these miRNAs and their putative target mRNAs in fast-and slow-twitch skeletal muscle of pacu during growth. We used pacus in three different development stages: larval (aged 30 days), juvenile (aged 90 days and 150 days) and adult (aged 2 years). To complement our study, we also performed a pacu myoblast cell culture, which allowed us to investigate miRNA expression in the progression from myoblast proliferation to differentiation. Our results revealed an inverse correlation between the expression of the miRNAs and their target mRNAs, and there was evidence that miR-1 and miR-206 may regulate the differentiation of myoblasts, whereas miR-133 may regulate the proliferation of these cells. miR-499 was highly expressed in slow-twitch muscle, which suggests its involvement in the specification of the slow phenotype in muscle fibers. The expression of these miRNAs exhibited variations between different development stages and between distinct muscle twitch phenotypes. This work provides the first identification of miRNA expression profiles in pacu skeletal muscle and suggests an important role of these molecules in muscle growth and in the maintenance of the muscle phenotype.